Magma evolution and PGE mineralization in the Late Neoproterozoic Mechanic Settlement Pluton, southern New Brunswick - Heibert, Russel; Barr, Sandra; Stanley, Clifford (Atlantic Geology, 2008)
Abstract The Mechanic Settlement Pluton, southern New Brunswick, is a high-level mafic-ultramafic pluton of Late Neoproterozoic age (ca. 557 Ma). Based on surface-outcrop and drill-core samples, the pluton includes six different lithologic assemblages: peridotitic, olivine-bearing gabbroic, gabbroic, anorthositic, troctolitic, and dioritic, each of which consists of a range of related rock types. Cumulate textures are typically present, and several rock types contain interstitial hydrous silicate minerals, indicating a wet parent magma. The general mineral crystallization sequence in the pluton was olivine and chromite, plagioclase, clinopyroxene, orthopyroxene, and a hydrous mafic silicate mineral (either phlogopite or hornblende). Lithologic assemblages and their constituent varieties are not continuous between drill holes, and no statistically significant pattern in the stratigraphic succession could be established with the available data. Variation in the mineralogy and chemistry of the rocks is controlled by fractionation of olivine and plagioclase. The Mechanic Settlement Pluton and comagmatic Coldbrook Group basalt are probably of calc-alkaline affinity. Several horizons bearing platinum-group elements associated with minor sulphide mineralization (pyrrhotite-chalcopyrite-pentlandite) occur in peridotitic rocks, which may have formed during or following magma influx. Based on similarities to the Lac des Iles complex, Ontario, the best potential for exploration for additional mineralization may be in the poorly exposed gabbroic-dioritic western part of the pluton.